Literature Review: Mosquito Vectors and Transmission of Filarial Worms Causing Lymphatic Filariasis in Kalimantan - Cecilia, Agnes (Program Studi Teknologi Laboratorium Medis, 2025)
Lymphatic filariasis is a chronic infectious disease caused by filarial worms and transmitted by mosquito vectors. Kalimantan is an endemic area for filariasis with various mosquito species and environmental factors contributing to its transmission. This study aims to identify dominant mosquito vector species and the environmental conditions that support the transmission of filarial worms in Kalimantan using a Systematic Literature Review approach. Relevant literature was gathered from scientific databases such as PubMed and Google Scholar, focusing on the last ten years. The results indicate that mosquito species such as Mansonia uniformis, Mansonia dives, Anopheles barbirostris, and several Culex species act as primary vectors in several provinces. Habitats like swamps, rice fields, and water pools, combined with factors such as warm temperatures, high humidity, nighttime activity, and reservoir hosts like cats, contribute to transmission risks. This review highlights the importance of ecological-based strategies for sustainable filariasis control in Kalimantan.